Tecnologias e metodologias ativas (res)significando percursos educacionais - Garcia, Daniela Nogueira de Moraes (Editora Oficina Universitária, 2022)
Talking about the teaching and learning process, at this moment, demands two preponderant aspects for reflection: our place of speech and our training course. Such issues are intertwined in such a way that conceiving one over the other would be the same as perceiving the material world only through the lens of events in loco, disregarding our experiences as sociocultural products, fruits of the accumulation of constructions, woven by the temporal overlap of the thick layers of History. In the middle of the 21st century, educational scenarios are transfigured with the same speed of technological advances and science, imposing on education professionals the re-signification of their practices that once had only chalk, blackboard and textbooks as resources. For Lévy (1999, p. 11), "[...] we are experiencing the opening of a new communication space, and it is only up to us to explore the most positive potential of this space in the economic, political, cultural and human planes." The use of digital information and communication technologies (TDIC), which has long been debated between researchers and teachers of Basic Education, become, in the face of the pandemic context, viable alternatives to ensure knowledge and, at the same time, offer students a minimum of learning in the midst of the sudden and, at times, desolate scenario established since 2020. According to Schneider (2015, p. 63), "[...] it is necessary to recognize these changes, understand them and insert technologies as resources that enhance the teaching and learning process in teaching practices." The focal point of this work lies in the moments of reflection established during the course of the subject Education and New Technologies: implications for the curriculum of Basic and Higher Education, taught by Professor Daniela Nogueira de Moraes Garcia, linked to the Postgraduate Program in Education (PPGE ), from Unesp in Marília. Between experiences, sharing and theoretical studies about the menu, in the end, students were challenged to legitimize their voices and their different places of speech in the form of an article or experience report, highlighting the use of techno-digital artifacts as tools capable of promoting learning, disruptiveness and empowerment of young people who are widely inserted in social practices mediated by the interface of their smartphones, tablets and notebooks. In this sense, Kalantzis et al. (2020, p. 358) point out that "[...] learning becomes more effective when the diverse perspectives of students are deliberately introduced into the classroom and used as resources." At no time did we allow ourselves to be glimpsed by the machines to the point of neglecting affectivity, the value of relationships and the constant exercise of active listening and dialogism between teachers and students, because "[...] through a critical pedagogy and revolutionary we can rescue the utopia expressed in a critical-emancipatory conception, in which there is the possibility of dialogue, interaction, transformation and change, in addition to meeting the challenges of the time to come" (CORRÊA, 2019, p. 12).